1993
DOI: 10.1021/bp00024a016
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fluorescence Cell Mass Measurements of Saccharomyces cerevisiae Using Cellular Tryptophan

Abstract: This work describes a new spectroscopic optical fiber/rod technique for in situ real time measurement of cell mass and product concentrations in bioreactors using intrinsic fluorescence. The variable excitation/emission wavelength capability of this sensor allows for species-selective measurement during fermentations. Cell mass (tryptophan) and product concentrations (pyridoxine) have been measured during fermentations of Saccharomyces cerevisiae. The effects of varying substrate concentration and oxygen conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 16 publications
1
25
0
2
Order By: Relevance
“…Based on literature it was possible to associate some regions of this map to specific fluorophors, namely Phe, Tyr, Trp , pyridoxine, and riboflavin Marose et al, 1998;García et al, 2001). In bioreaction culture bulks, the maximum fluorescence emission for Trp normally reported corresponds to excitation at 290 nm Horvath et al, 1993;Surribas et al, 2006c). However, the maximum fluorescence signal for each fluorophor changes with the environmental conditions .…”
Section: Process and 2d Fluorescence Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on literature it was possible to associate some regions of this map to specific fluorophors, namely Phe, Tyr, Trp , pyridoxine, and riboflavin Marose et al, 1998;García et al, 2001). In bioreaction culture bulks, the maximum fluorescence emission for Trp normally reported corresponds to excitation at 290 nm Horvath et al, 1993;Surribas et al, 2006c). However, the maximum fluorescence signal for each fluorophor changes with the environmental conditions .…”
Section: Process and 2d Fluorescence Dynamicsmentioning
confidence: 99%
“…Fluorescence signal from intracellular proteins (Horvath et al, 1993) and from vitamins (Hisiger and Jolicoeur, 2005a) have been successfully used to monitor microbial growth. The fluorescence of NAD(P)H has been used preferentially for monitoring cellular activity since their concentration within cells depends on cells' metabolic state Tartakovsky et al, 1996;Marose et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these experiences, miniaturized fluorimetric probes were built [28][29][30]41] mainly for the monitoring of the NAD(P)H dependent fluorescence. Only few systems were described where different wavelenghts could be monitored [30,42,43]. Even when these techniques offer the possibility to non-invasively monitor the metabolic state of the cultivated microorganisms, the signal interpretation was often difficult.…”
Section: -D-fluorescence Monitoringmentioning
confidence: 99%
“…13 -16 It has been reported that the tryptophan fluorescence signal from intracellular protein structures in Saccharomyces cerevisiae can be used to monitor cell growth. 17 This shows some advantages over NADH fluorescence, as it is not so dependent upon the cell's metabolic state. Other works have analysed the possibilities of fluorometry for monitoring purposes in bioprocesses yielding a moderate cell density level.…”
Section: Introductionmentioning
confidence: 99%